Discrete and 1D Polymeric Copper(II) Complexes of Tetranuclear Cubane‐like Units: Structural and Magnetic Characterization. Issue 34 (11th September 2018) - Manna, Subal Chandra; Manna, Soumen; Mistri, Soumen; Patra, Apu; Zangrando, Ennio; Puschmann, Horst; Goddard, P. A.; Ghannadzadeh, S.
Abstract: Two novel copper(II) complexes, [Cu4 (L)2 (LH)2 (H2 O)2 ]2 (NO3 )2 . (pydc).9H2 O (1 ) and {[Cu4 (L)2 (LH)2 (H2 O)2 (ppda)].5H2 O}n (2 ) [H2 L=2‐[(2‐hydroxy‐ethylimino)‐methyl]‐6‐methoxy‐phenol, pydc=pyridine‐3, 5‐dicarboxylate, ppda=phenylene‐1, 4‐diacrylate]have been synthesized and characterised by X‐ray single crystal diffraction analysis and low temperature magnetic study. The structural determination reveals for complex1 a tetranuclear species exhibiting a double‐open cubane like core framework, whereas use of ppda anions results 1D coordination polymer where tetranuclear double‐open cubane cores are connected by bridging ppda ligands. In both the complexes, hydrogen bonding interactions lead to 3D supramolecular structures. Low temperature magnetic study indicates antiferromagnetic coupling in both the complexes. A model based on an effective square tetramer of Heisenberg spins was used to determine exchange strengths of 174(2) K for1 and 107.4(4) K for2 . Abstract : Discrete copper(II) complex and 1D coordination polymer (obtained by bridging dicarboxylate anions), comprising tetranuclear double‐open cubane like core, have been synthesised and structurally characterised. Magnetic study indicates antiferromagnetic coupling in both the complexes and the exchange strengths were determined with a model based on an effective square tetramer of Heisenberg spins.